Regularities of hydrogen accumulation and distribution in titanium coatings formed on a steel substrate by the cathode-arc method - Kopyrina, A.V.; Abdyr, A.S. (Recent Contributions to Physics, 2021)
The main direction in the field of the use of hydrocarbon resources is the creation of a metal hydride hydrogen battery. Hydrides are solid non-volatile substances that are formed when certain metals are combined with hydrogen. The principle of using hydrides as a medium for storing hydrogen is simple: under pressure, the metal captures hydrogen, which dissolves in the metal, forming a new chemical, and when the hydride is heated, the gas is given back. The metal hydride method of hydrogen storage is based on the ability of a number of intermetallic compounds, metals, alloys and composite materials to reversibly and selectively absorb hydrogen. The object of the study is titanium coatings formed on samples of 12X18H10T stainless steel by the cathode-arc method. In the course of the study, ion-plasma deposition of coatings was carried out. Scanning electron microscopy was also performed. The phase composition and structure of the titanium coating in the initial and submerged state were evaluated. Gas-phase hydrogenation was carried out, followed by an assessment of the effect of hydrogen on the alloy structure. Titanium was deposited by the cathode-arc method. Deposition of titanium coatings was carried out on the Raduga-Spektr installation, microstructure analysis was carried out on SEM using a Hitachi TM–2800 gas-phase hydrogen saturation microscope using an automated Gas Reaction Controller complex, a Shimadzu XRD-7000S diffractometer, and an inert gas melting method using a LECO RHEN 602 hydrogen analyzer.